Kazakhstan-Russia: Enduring eurasian defence partners - Roger N. McDermott (Danish Institute for International Studies (DIIS), 2012)
This report is intended to inform policymakers of the aims, scope and changing dynamics in the complex and evolving defence and security relationship between Kazakhstan and Russia. This analysis will also prove of interest to any specialist or student of the development of Central Asia generally or Kazakhstan specifically since its independence in 1991.
Keywords: 300